Expression of BCL2 alternative proteins and association with outcome in CLL patients treated with venetoclax. Issue 5 (16th April 2021) - Marques-Piubelli, Mario L.; Schlette, Ellen J.; Khoury, Joseph D.; Furqan, Fateeha; Vega, Francisco; Soto, Luisa M. Solis; Wistuba, Ignacio I.; Wierda, William G.; Konopleva, Marina; Ferrajoli, Alessandra; Strati, Paolo
Abstract: Venetoclax, a BCL-2 inhibitor, is highly effective for the treatment of patients with chronic lymphocytic leukemia (CLL) and dependence on alternative proteins may result in resistance to BCL-2 inhibition. Patients with CLL treated with venetoclax as monotherapy at MD Anderson Cancer Center between 05/2012 and 01/2016 were included and pretreatment bone marrow was analyzed by immunohistochemistry (IHC) for BCL-W, BCL-XL, BCL2-A1 and MCL-1. Twenty-seven patients were included. BCL-W + and BCL-2A1+ was found in 15% and 7% of the patients, respectively. Both BCL-XL and MCL-1 were negative in all samples. A higher CR and longer PFS rates were observed in patients with BCL-W+ ( p = .60, p = .46), BCL-2A1+ ( p = .60, p = .29), and either BCL-W + or BCL-2A1+ ( p = .33, p = .20), though not statistically significant. Pretreatment IHC expression of BCL-2 alternative proteins does not predict response to venetoclax in CLL, but may be a surrogate for an indolent biology. Sensitive techniques are needed to explore anti-apoptotic pathways.